2012
DOI: 10.1177/1359105312440298
|View full text |Cite
|
Sign up to set email alerts
|

Being men with eating disorders: Perspectives of male eating disorder service-users

Abstract: This study aimed to explore experiences of men currently using eating disorder services. Eight men from two eating disorder services were interviewed about their experiences of seeking and receiving treatment. Two superordinate themes emerged from Interpretative Phenomenological Analysis: (1) difficulty seeing self as having an eating disorder; and (2) experiences of treatment: how important is gender? The underlying themes varied in their specificity to men, with some echoing findings from the female eating d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
144
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(151 citation statements)
references
References 40 publications
4
144
0
Order By: Relevance
“…A further implication is that the role of femininity in mens' body dissatisfaction and disordered eating should not be neglected. Masculinity is frequently mentioned in discussions of male body image and eating disorders (Blashill, 2011;Robinson, Mountford, & Sperlinger, 2013), and the results of the present study suggest that similar scrutiny should be directed toward femininity. Comprehensive examination of gender role conformity through examination of norms for both genders may be particu larly important for body image and eating disorders, given evi dence that these conditions are heavily subjected to gender role stereotypes .…”
Section: Discussionmentioning
confidence: 71%
“…A further implication is that the role of femininity in mens' body dissatisfaction and disordered eating should not be neglected. Masculinity is frequently mentioned in discussions of male body image and eating disorders (Blashill, 2011;Robinson, Mountford, & Sperlinger, 2013), and the results of the present study suggest that similar scrutiny should be directed toward femininity. Comprehensive examination of gender role conformity through examination of norms for both genders may be particu larly important for body image and eating disorders, given evi dence that these conditions are heavily subjected to gender role stereotypes .…”
Section: Discussionmentioning
confidence: 71%
“…Males experiencing high levels of body dissatisfaction may be subject to greater stigmatisation, or experience more self-stigma than females with similar levels of body dissatisfaction, as research has demonstrated the presence of stigma and self-stigma among males with eating disorders, [22][23][24][25] and stigma surrounding body dissatisfaction and body image among high school boys. 26 The experience of stigma may contribute to the manifestation of poorer QoL among males than females at comparable levels of body dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence on gender differences in prognosis is limited, one recent cohort study found treatment outcomes in all EDs were better for men than women, when remission was measured by weight restoration and self-reported relapsing 21. Some studies suggest that men with EDs are more likely to engage in obsessive exercise15 17 19 22 and have more psychiatric morbidity as a result of an ED 15 19. Homosexuality has also been cited in some studies as a risk factor for men 15 17 23…”
Section: Introductionmentioning
confidence: 99%